Curtindo os curtas : análise da construção de imagens discursivas de Aracaju e de aracajuanos em curtas-metragens - Santana, Flávio Passos (2017)
The texts bear indications of who is speaking, who is addressed and, also, of the social groups to which these subjects belong to. In the texts that state Aracaju this is no different. Thus, we took this as a starting point for our work which is one of the elements of the Aristotelian triangle of persuasive discourse, ethos - the image that the speaker constructs of himself in his discourse - that can be related to the discursive identity and that has been the focus of study in neo-rhetorical and discursive theoretical approaches. Thus, we try, from this proposal, to answer the following questions: (i) what is the discursive identity inherent in Aracaju? (Ii) and what is inherent to the Aracajuanos ?; (Iii) how are discursive images constructed in short movies produced in this city? We intend to analyze images linked to our city through two short movies produced by sergipeans, Isaac Dourado, Arthur Pinto and André Aragão: "Xandrilá" and "Madona e a cidade paraíso ". For this, we adopted as theoretical presuppositions, in this research, Aristotle's Argumentation and Rhetoric studies (2011 [384-322 BC]); Perelman and Olbrechets-Tyteca (2005 [1958]); Mosca (1999). Trying to merge them with the concept of intertextuality proposed by Bakhtin (2015 [1992]); Koch; Bentes; Cavalcante (2008), insofar as all text can resume other texts, which ends up showing an analogy between its interior and its exterior. Because of this, it gives us the possibility to understand how the discursive images present in the short movies were created. We also based our studies on Maingueneau (2005) and Amossy (2005), in order to give an extension of the concept of Aristotelian ethos. In Greimas and Courtés (2013 [1993]), as well as Barros (2012), we bought concepts of greimasian semiotics, and in Padovan (2001); Bernardet (1985 [1936]); Xavier (2012); Metz (1972) studies on cinema and / or short films. In order to obtain the desired results, we opted for the verbal and non-verbal analysis of some scenes of the short films in question, taking as a criteria for this clipping the opposition between sacred and profane. The same criteria was used to cut songs that make up the soundtrack. From these excerpts, we analyzed, in particular, the intertexts present in the films, considering intertextuality as an important strategy in the definition of ethé. The themes dealt with and their concretions in figures, scenography, and other diverse strategies that, along with intertextuality, could reveal the ideologies, values and beliefs of speaker and audience and indicate the discursive identities, ethé, that emerge from them was also considered in the analysis. The ethos revealed by the texts are, on one hand, the people who do not follow the standards of life imposed by society and, on the other hand, those who marginalize the former and conform to the behaviors considered appropriate to society. The ethos of the implied authors, the producers, as well as their audience, are still revealed, who are faithful to the origin of the short films and concerned with solving the problems that occurred in the city in which they live. With the result of these analyzes, we hope that by disseminating imagery and discursively the city, its history, its values, its culture and its people, there will be a significant diffusion of the knowledge about this region in several areas of activity.